Bahasa Asing Sebagai Simbol Status Dalam Realita Di Indonesia Modern - Elza Leyli Lisnora Saragih purba; Nuryosianna Putri Purba; Diapita Br Sitepu; Wina Ayusari Tambun (MUARA PENDIDIKAN : Jurnal Ilmiah Ilmu Pendidikan & Sosial Humaniora, 2025)
This study examines the role of foreign languages, particularly English, as a status symbol in the reality of modern Indonesian society through an analysis of the use of foreign languages in branding and advertising. A case study of the “Sweet Choco Macaron” advertisement shows that English is used predominantly in various elements of the advertisement, from the product name and description to promotional offers, which not only function as a communication tool but also as a marker of modernity and social status. The use of foreign terms such as “macaron,” “extraordinary taste,” and “special offer” strengthens the product’s image as a premium item that adheres to international standards, and targets urban consumers who associate the consumption of foreign-labeled products with a global lifestyle and a higher social class. Sociolinguistically, this phenomenon reflects a shift in values in urban Indonesian society, where foreign languages become symbolic capital to build brand image, increase product appeal, and differentiate consumers based on social status and lifestyle. Research on television advertisements shows that the majority of advertisements incorporate foreign languages as an effective marketing strategy to build product exclusivity and prestige. However, the dominance of foreign languages in advertisements also poses challenges to the preservation of Indonesian as a national identity. Therefore, proportional efforts are needed to integrate Indonesian and foreign languages in the commercial sphere in order to maintain the integrity of the national language and culture amidst the current of globalization.